Method of Nursing Interventions to Reduce the Incidence of Bullying and Its Impact on Students in School : A Scoping Review - Iyus, Yosep; Rohman, Hikmat; Ai, Mardhiyah; Helmy, Hazmi; Taty, Hernawaty (MDPI, 2022)
The bullying of students in schools can have a negative impact on students. The impact of bullying can take the form of anxiety, low psychological well-being, low social adjustment, psychological distress, and risk of suicide. Incidents of bullying are still considered normal, and there has not been a focus on reducing their incidence and impact. The purpose of this study is to describe nursing interventions to reduce the incidence of bullying and its impact on students at school. This study used the scoping review method and literature reviews via CINAHL, PubMed, and ProQuest databases. The keywords used in English were “bullying OR cyberbullying OR aggression” AND “students OR school students” AND “school OR schools” AND “nursing intervention”. The criteria for articles in this study were: full texts, student populations and samples, randomized control trials or quasi-experiment research designs, use of the English language, and the publication period of the last 10 years (2013–2022). We found 11 articles discussing nursing interventions to reduce the incidence of bullying and its impact on students in schools. There are four types of interventions that can be provided to students, namely, prevention programs, activities programs, peer group programs, and resilience programs. Most of the articles used randomized control trials and quasi-experiment designs. The samples in the articles analyzed were in the range of 50–7121 students. These four types of interventions can reduce the incidence of bullying and its impact on students at school, and in addition, they can improve the social skills and mental health of students, for example, by increasing their self-efficacy, resilience, and adaptive coping. There are four nursing interventions to reduce the incidence of bullying and its impact on students in schools, namely, the prevention program, activities program, peer group program, and resilience program.